2019
DOI: 10.2478/ats-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of women participation in farmer group activities in Kwara State, Nigeria

Abstract: The level of access of women to production resources can be enhanced through their active membership and participation in farmers’ associations. However, most farmer-groups in Nigeria are male-dominated. The study therefore analysed women farmers’ participation in farmer-group activities in Kwara State. Specifically, the study identified the expectations of women from group membership; determined their level of participation; identified constraints to participation; and investigated the determinants of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
2
2
0
1
Order By: Relevance
“…In other words, active age of the women was an incentive to their active participation in farming activities. The finding concurred with Omotesho, et al [12]; Adams [9] that age had a positive coefficient which suggested that as the age increased, the participation of women in agricultural production increased.…”
Section: Agesupporting
confidence: 88%
See 2 more Smart Citations
“…In other words, active age of the women was an incentive to their active participation in farming activities. The finding concurred with Omotesho, et al [12]; Adams [9] that age had a positive coefficient which suggested that as the age increased, the participation of women in agricultural production increased.…”
Section: Agesupporting
confidence: 88%
“…Farm size was positively and significantly related. This corresponded Enete and Amusa [8]; Omotesho, et al [12] that the access to farmland made women to contribute to decision making in household.…”
Section: Farmland Sizesupporting
confidence: 64%
See 1 more Smart Citation
“…Hasil penelitian di Nigeria menyebutkan tingkat partisipasi wanita tani dalam pembiayaan mikro usahatani dipengaruhi oleh besarnya iuran bulan dan peran ketua kelompok (Anyiro et al, 2014). Masalah keuangan, kurangnya rasa memiliki, waktu kegiatan yang tidak tepat dan diskriminasi sosial budaya merupakan faktor-faktor yang dapat menghambat partisipasi wanita tani dalam suatu kegiatan (Omotesho et al, 2019)…”
Section: Pendahuluanunclassified
“…Several studies confirm the influence of socio-economic characteristics of individuals and some characteristics of groups on the participation of members in groups. Members' age, educational status, household size, marital status, income, farming experience, farm size, membership size, age of group are some of the variables that have been investigated as factors that could influence the participation of members in groups (Abegunde, 2009;Agbonlahor et al, 2012;Ofuoku, 2013;Omotesho et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%